Theology on the border: the Mediterranean, minority identity and migration - Rapisarda, Daniela Lucia (New critical thinking in religion, theology and biblical studies, 2025)
"Focusing on the Mediterranean, this book offers a theological hermeneutic from the perspective of the margin/border, and a theological hermeneutic of the border. At the core is a case study of the Italian Protestant minority and its engagement with issues of migration. While much of current migration theology is built around the principle of sacralization of the migrant person or 'vertical' association between divinity (God or Jesus) and people on the move, this work offers a 'horizontal' perspective on humanization or recognition of the value of every human being, based on the principle of a shared humanity created in God's image, and a sense of identification, first by people at the margins. This approach seeks to avoid essentializing migrantness and victimhood. Elaborations on the relation between identity and migration are often sustained by exclusionary logics that lead to repressive policies. The book proposes a contextual theological reflection on minority identity that is at its core inclusive. It offers a contribution to theology beyond confessional borders and is open to dialogue with other disciplines, particularly critical border studies"--